Antiviral effects of PNA in duck hepatitis B virus infection model - Chen Zong-yan; Cheng An-chun; Wang Ming-shu; Xu Da-wei; Zeng Wen; Li Zhan (Acta Pharmacologica Sinica; Vol 28, No 10 (October 2007): Acta Pharmacologica Sinica, 2016)
Aim: To study the efficacy of antiviral treatment with PNA for the duck model of HBV (DHBV)-infected ducks. PNA is a 2-amine-9-(2,3-dideoxy-2,3-dihydro-beta-D-arabinofuranosyl)-6-methoxy-9H-purine. Methods: The Sichuan Mallard ducklings in the hepatitis B virus model were treated with PNA, a new antiviral agent. DHBV DNA from the blood serum and liver tissues were measured at 0, 5, and 10 d during the treatment and at 3 d withdrawal by real-time PCR. The duck hepatitis B surface antigen (DHBsAg) in the liver cells was observed by Immunohistochemistry (IHC). Pathological changes in the liver tissues were also observed. Control group I was administered with distilled water and control group II was administered with 3-thiacytidine. Treatment group I was administered with PNA at a dose of 40 mg/kg and treatment group II was administered perorally (po) with PNA at a dose of 80 mg/kg. Treatment group III was administered with PNA at a dose of 20 mg/kg and treatment group IV was intravenously administered with PNA at a dose of 40 mg/kg. Each group contained 15 ducklings. Results: PNA can significantly lower the DHBV replication levels in serum and liver. Compared with control group II, there were no significant differences in inhibiting efficacy in treatment groups I and III (P>0.05) and there were significant differences in inhibiting efficacy in treatment groups II and IV (P